2015
DOI: 10.1116/1.4915263
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of different sample preparation routes for mass spectrometric monitoring and imaging of lipids in bone cells via ToF-SIMS

Abstract: In ToF-SIMS analysis, the experimental outcome from cell experiments is to a great extent influenced by the sample preparation routine. In order to better judge this critical influence in the case of lipid analysis, a detailed comparison of different sample preparation routines is performed—aiming at an optimized preparation routine for systematic lipid imaging of cell cultures. For this purpose, human mesenchymal stem cells were analyzed: (a) as chemically fixed, (b) freeze-dried, and (c) frozen-hydrated. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…Fluorescent probe-free techniques such as mass spectrometry, Raman spectroscopy, and, as already mentioned, EM can be used to circumvent some of these issues. However, these techniques require cell fixation and longer acquisition times as well as a high degree of expertise and sophisticated equipment [73, 80, 81]. A different set of fluorescent ratiometric probes, which are sensitive to differences in physicochemical membrane properties and can distinguish between a spectrum of tightly packed raft and relatively fluid non-raft domains, include Laurdan and ANEP (e.g., di-4-ANEPPS, di-4-ANEPPDHQ, and di-8-ANEPPS) dyes.…”
Section: Plasma Membrane Micro- and Nanodomain Structure And Organizamentioning
confidence: 99%
“…Fluorescent probe-free techniques such as mass spectrometry, Raman spectroscopy, and, as already mentioned, EM can be used to circumvent some of these issues. However, these techniques require cell fixation and longer acquisition times as well as a high degree of expertise and sophisticated equipment [73, 80, 81]. A different set of fluorescent ratiometric probes, which are sensitive to differences in physicochemical membrane properties and can distinguish between a spectrum of tightly packed raft and relatively fluid non-raft domains, include Laurdan and ANEP (e.g., di-4-ANEPPS, di-4-ANEPPDHQ, and di-8-ANEPPS) dyes.…”
Section: Plasma Membrane Micro- and Nanodomain Structure And Organizamentioning
confidence: 99%
“…3,4 Since ToF-SIMS operates under an ultrahigh vacuum environment, biological samples such as cells and tissues should be properly prepared to be compatible with vacuum conditions, such as by chemical xation followed by dehydration, freeze drying, or frozen hydration method. [5][6][7][8] Compared to chemical xation, frozen hydrated sample preparation has been more recognized for preserving cell morphology and native distribution of molecules including diffusible ions, as well as for enhancing molecular ion intensities for phospholipids for ToF-SIMS imaging of hydrated cells. 9,10 Despite the aforementioned advantages, a frozen hydration method requires laborious, painstaking procedures for reproducible results, as well as special equipment like a liquid nitrogen cooled stage to keep samples frozen during the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on cell analysis have compared various preparation methods focusing on different aspects in order to maintain sample integrity and to reduce analytical artifacts. [2][3][4][5][6][7][8][9][10][11][12] Such studies are necessary to ensure that differences in measured spectra are due to true sample differences (e.g., "healthy" versus "diseased" cells) and not sample preparation-induced artifacts. It was inter alia revealed that frozen-hydrated analysis of freeze-fractured cells is the goldstandard for adequate detection of diffusible elements in cells.…”
Section: Introductionmentioning
confidence: 99%
“…6 Still, this method struggles with problems in terms of complexity, reproducibility, and applicability to a large a) Electronic mail: Marcus.Rohnke@phys.chemie.uni-giessen.de number of samples. 3,11,13 For these purposes, chemical fixation and freeze-drying have proven to be beneficial. 11,14,15 In addition, to obtain reliable results from biological samples, it is important to minimize their natural intrinsic variance by ensuring comparable conditions at all times prior and during measurement.…”
Section: Introductionmentioning
confidence: 99%